The Magnificent VWF SNPs and Where to Find Them: A Journey in Exon 28 of the Hispanic Population. (11th September 2019) - Barouqa, Mohammad; Choudhuri, Jui; Fecher, Roger; Jacob, Jack; Sadeghi, Saed; Gil, Morayma Reyes
Abstract: von Willebrand disease (VWD) is a common coagulation disorder with a prevalence of 0.1% to 1.0% manifesting as a wide spectrum of bleeding symptoms. Type 1 is diagnosed by confirming a quantitative decrease in VWF level, while type 3 has undetectable levels of VWF. Type 2 VWD variants are characterized by functional and binding defects. Initial diagnosis and follow-up depend mainly on measuring VWF protein and VWF activity and calculating the activity to protein ratio. Ristocetin cofactor activity (VWF:RCo) is the most widely used and gold standard activity assay. In our institute, we use a cutoff of VWF:RCo/VWF:Ag <0.7 to screen for possible type 2 VWD. However, the use of this ratio is flawed by the presence of specific SNPs (I1380V, N1435S, and D1472H) in the A1 domain, especially in African Americans. These SNPs lead to a decrease in ristocetin binding to VWF and hence decreased VWF:RCo/VWF:Ag ratio. In this retrospective study, we analyzed the levels of VWF:AG and VWF:RCo based on patients' ethnicity using an in-house data mining software from 2011 to 2016. Then, we validated several exon 28 primers, kindly provided by Dr. Montgomery (Blood Center of Wisconsin), used to detect type 2 mutations and SNPs in African Americans. We excluded cases diagnosed as positive for VWD and included only cases rendered nondiagnostic of VWD following a comprehensive panel including multimers, collagen binding, and molecular studies when indicated. In our Hispanic population (n = 936), VWF:Ag was 138.9% and 117% (average and median) and VWF:RCo was 110.5% and 93.0% (average and median); 43.2% of Hispanics had VWF:RCo/VWF:Ag <0.7. In our African American population (n = 664), VWF:Ag was 163.0% and 138.5% (average and median) and VWF:RCo was 108.5% and 92.0% (average and median); 50.6% of the African American patients had VWF:RCo/VWF:Ag <0.7. Patients from Caucasian origins (n = 242) had VWF:Ag of 149.6% and 113.0% (average and median) and VWF:RCo of 137.6% and 116.0% (average and median), respectively; 30.9% of Caucasian patients had VWF:RCo/VWF:Ag of less than 0.7. We then selected four random Hispanic cases with VWF:RCo/VWF:Ag <0.5 as part of the validation study of exon 28 sequencing. Using a Sanger sequence assay, we found multiple benign/likely benign single-nucleotide polymorphisms (SNPs) at exon 28 that code for VWF antigen A1 domain. All four cases showed P.Thr1381Ala and P.Thr1547 = [OC1] polymorphism, three showed p.Val1565Leu polymorphism, and two showed p.Ala1555 = polymorphism. The statistical analysis of VWF:Ag/VWF:RCo levels from Hispanics shows a similar trend to African Americans with a high rate of cases with VWF:RCo/VWF:Ag <0.7 in comparison to Caucasians. However, the finding of SNPs and absence of known African American polymorphisms suggest that these SNPs may be the cause of decreased ristocetin binding in Hispanics. This study calls for ethnic-based considerations in VWD workflows.